Multielemental Analysis of Important Tibetan Medicine Gentiana straminea from Qinghai-Tibet Plateau - Sun, Jing; Zhou, Yubi; Xu, Qingcai; She, Liping; Lu, Xuefeng; Ye, Runrong; Sun, Shengnan; Zhao, Qingshuai; Peng, Min (Asian Journal of Chemistry, 2014)
Here, we identified 17 elements in samples of the important Tibetan medicinal herb Gentiana straminea, which were collected from 28 different locations throughout the Qinghai Plateau of China. The samples were dissolved in HNO3 and H2O2 for inductively coupled plasma-atomic emission spectrometry (ICP-AES) analysis. For each element, the analysis lines with the highest sensitivity and lowest interference spectrums were chosen. Recovery of samples ranged from 93 to 106 %, indicating the accuracy of the analysis. The mean concentrations of the 17 elements were as follows: Ca > K > Mg > Ba > Fe > Na > Al > Zn > Cu >Mn> V > Ni > Ti > As > Sn > Cd > Co. Quantitative analysis of the identified elements was also performed to elucidate the elemental characteristics and influences of geographical distribution. The results indicated that K, Zn, Mg and Ca were the main characteristic elements of this herbal medicine and each analyzed element showed significant variations among the different geographical locations. Our results provide a scientific foundation for the utilization and further research of G. straminea.